Short-term effect of hand-arm vibration exposure on tactile sensitivity and manual skill - Thonnard, J.-L.; Masset, D.; Penta, M.; Piette, A.; Malchaire, J. (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'The present study investigated whether the impairment of tactile sensitivity after exposure to vibration disturbs the motor control of precision handling and, if so, whether it can result in an increased risk of injury during or after tasks involving the use of vibrating tools.' ' METHODS ': 'Twelve men were manually exposed to vibration from an electric sander for 30 min. Cutaneous sensitivity was quantified by measuring the pressure perception threshold and vibration perception threshold (125 Hz) on the pulp of the second finger. Manipulative skill was evaluated by grip-lift movements and the Purdue pegboard test.' ' RESULTS ': 'The vibration perception threshold increased very significantly from 94.0 dB (0.06 m/s2) before the vibration exposure to 127.5 dB (3.2 m/s2) immediately after the exposure. The pressure perception threshold tended to increase after vibration exposure, although not significantly, but manipulative skill was not altered.' ' CONCLUSION ': 'Change in vibration perception threshold was not associated with a significant increase in the pressure perception threshold or a perturbation of manual skill. Therefore, in conditions similar to those of our experiment, the safety of a precision task does not appear to be reduced after such vibration exposure.
Keywords: manual dexterity; mechanoreceptive unit; precision grip; pressure perception; vibrotactile perception